Applied Mathematics in researches from the Instituto de Ciencia Animal. Fifty years of experience - Torres, Verena; Cobo, Raúl (Cuban Journal of Agricultural Science, 2016)
This study reviews advances in Applied Mathematics, developed between 1973 and 2014, at the Instituto de Ciencia Animal, and published in the Cuban Journal of Agricultural Science. These contributions are about estimation and hypothesis testing, experimental designs, informatics and automatic systems, sampling techniques and sample size, mathematical simulation and modeling, econometrics and multivariate methods. During the cited period, the percentages of articles per subject were 8.4, 11.6, 5.3, 16.8, 27.4, 13.7 and 16.8, respectively. Modeling and simulating, sampling techniques and sample size, and multivariate methods were the most published subjects.Keywords: Biometry, Economy and Informatics